ECONOMIC DIPLOMACY AS AN APPROACH TO SUSTAINING OIL COOPERATION BETWEEN IRAQ AND CHINA (World Economics and Finance Bulletin, 2026)
This research aims to examine the role of economic diplomacy as an approach to achieving sustainable oil cooperation between Iraq and China. The study revealed that oil cooperation between the two countries has evolved beyond mere trade transactions into a long-term strategic partnership reliant on effective diplomatic tools, such as bilateral agreements and joint committees, to mitigate economic and political risks. The field study (a questionnaire) indicated that the majority of participants believe economic diplomacy is essential to ensuring the sustainability of oil cooperation, despite potential challenges including regional political instability and environmental issues, the effects of which can be mitigated through structured diplomatic and technical strategies. The research findings also demonstrated widespread optimism regarding the future prospects of cooperation, including expanding the partnership to encompass downstream oil industries and linking it to development initiatives such as the Belt and Road Initiative. Therefore, the research underscores the necessity of strengthening Iraq's diplomatic and economic capabilities to guarantee the continuation of oil cooperation and the achievement of sustainable economic development goals.